Idiosyncratic Risk in Corporate Finance: A Global Research Landscape - Indra Halim; Yana Priyana; Muhamad Ammar Muhtadi; Muhammad Fithrayudi Triatmaja; Ferlinda Ainur Rachmani (Sanskara Ekonomi dan Kewirausahaan, 2026)
This study aims to map and analyze the global research landscape of idiosyncratic risk in corporate finance using a bibliometric approach. Data were retrieved from the Scopus database and analyzed using VOSviewer software to examine publication trends, co-authorship patterns, institutional collaborations, country contributions, and keyword co-occurrence structures. The findings indicate that research on idiosyncratic risk is highly concentrated within a core intellectual structure dominated by corporate finance, asset pricing, and financial market theories. Co-authorship and institutional analyses reveal a significant dominance of U.S.-based authors and universities, while emerging contributions from countries such as China, Germany, and India highlight increasing global participation. Keyword analysis shows that the field has evolved from foundational studies on volatility and market efficiency toward more interdisciplinary themes, including behavioral finance, corporate governance, and macroeconomic policy. The study concludes that idiosyncratic risk research has developed into a mature and expanding field that integrates multiple dimensions of financial economics and corporate decision-making.